1999
DOI: 10.1007/s002210050822
|View full text |Cite
|
Sign up to set email alerts
|

Grip force dynamics in the approach to a collision

Abstract: This experiment investigated the prediction of load force (LF) in impulsive collisions inferred from anticipatory adjustments of grip force (GF) used to stabilise a hand-held object. Subjects used a precision grip to hold the object between thumb and index finger of their right hand and used the arm either: (1) to move the object to produce a collision by hitting the lower end of a pendulum, causing it to swing to one of three target angles, or (2) to hold the object still while receiving a collision produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 3 publications
6
28
0
Order By: Relevance
“…Turrell et al (1999) and Li and Turrell, (2002) proposed that when receiving a collision -as would occur when playing a defensive stroke -the changes in grip forces are minimal prior to bat -ball contact, whereas large changes occur post-impact due to a latency reflex to prevent the bat from slipping from the hand. When producing a collision -as occurs when performing an attacking stroke -peak grip forces were observed at impact to ensure forces are transferred to the ball.…”
Section: Biomechanics and Cricket Batting 315mentioning
confidence: 99%
“…Turrell et al (1999) and Li and Turrell, (2002) proposed that when receiving a collision -as would occur when playing a defensive stroke -the changes in grip forces are minimal prior to bat -ball contact, whereas large changes occur post-impact due to a latency reflex to prevent the bat from slipping from the hand. When producing a collision -as occurs when performing an attacking stroke -peak grip forces were observed at impact to ensure forces are transferred to the ball.…”
Section: Biomechanics and Cricket Batting 315mentioning
confidence: 99%
“…In healthy subjects, equivalent results were found by Hermsdörfer and Blankenfeld (2008) who argue that continuous sinusoidal load changes are predictable due to their repetitive time course and therefore do not solely rely on reactive mechanisms. These authors hypothesize that during external load changes reactive and predictive mechanisms are combined in a flexible way depending on task conditions (see Hermsdörfer and Blankenfeld 2008;Turrell et al 1999). In addition, the updating of the ongoing grip-force response may require a shorter time than its initiation in sudden load steps (Johansson et al 1992a).…”
Section: Anticipation Of Externally Versus Self-generated Loadsmentioning
confidence: 99%
“…The finding of impaired precision during sinusoidal and sinusoidal-like loads leaves open the possibility that reaction during rapid load changes that occur at arbitrary time points-as for example tested in catching and illusion experiments (Nowak et al 2004;Turrell et al 1999)-may be better preserved following cerebellar damage. Therefore in a second control experiment sudden externally generated load jumps were produced.…”
Section: Rapid External Load Stepmentioning
confidence: 99%
“…Typically, when unpredictable loads are applied to a handheld object, feedback is used to track inertial changes and make appropriate grip force adjustments (e.g., Cole and Abbs 1988;Delevoye-Turell et al 2003;Johansson and Westling 1988;Johansson et al 1992a,b;Macefield and Johansson 1996;Nowak 2004;Serrien et al 1999;Turrell et al 1999). Consistent with this finding, we observed that when stepping on an unpredictable, pliant obstacle, peak grip force lagged peak inertial force by ϳ95 ms, indicating that feedback may be used to generate an appropriate response (Cole and Abbs 1988;Westling 1984, 1987).…”
Section: Grip and Inertial Forces Remain Synchronized During Predictamentioning
confidence: 99%